PROSEDUR PELAKSANAAN PENGAMPUNAN PAJAK (TAX AMNESTY) OLEH WAJIB PAJAK ORANG PRIBADI WBW PERIODE KEDUA TAHUN 2016 - Devi Purnama Sari; Yanuar Adi Putra; Vivi Gustiani (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2017)
In an effort to increase state revenues from the tax sector through tax intensification and extensification, one of them is the tax amnesty policy. This writing intends to find out the Procedure for Implementing Tax Amnesty by the WBW Personal Taxpayer for the second period of 2016. In this writing, it describes, calculates and calculates the basis for ransom fees in the implementation of tax amnesty on WBW individual taxpayers who have other business and income with work